Impact of Lithium Carbonate Spot Price Fluctuations on Electric Vehicle Sales: Comparing Emerging And Developed Markets - Kousa, Maria (My University, 2025)
With increased sustainability goals, the demand for electric vehicles has increased, as they are considered to be the more sustainable option compared to internal combustion engine vehicles. No prior studies were identified that examined the relationship between the price of lithium carbonate and electric vehicle sales in different markets. The purpose of this research is to analyze lithium carbonate spot price fluctuations impact on electric vehicle sales. As there are differences in consumer behavior and purchase power between different markets, the results are compared between emerging and developed markets to investigate differences between them and to see if lithium carbonate spot price can forecast electric vehicle sales in different markets. Three countries from each market are chosen and their electric vehicle sales, GDP per capita and different incentives are used to examine their differences during 2021–2024. This study uses a quantitative method to investigate secondary accessible public data through different statistical analysis methods. Theories, such as law of supply and demand, cost pass-through, as well income elasticity of demand, are used to help in analyzing the findings. In this study, descriptive analysis provides a simple understanding of the data gathered and its trends, which aids in providing a foundation for the next analyses methods that test the hypotheses and ultimately give answers to the research question. While comparative analysis is used to compare the differences of electric vehicle sales in emerging and developed markets, a correlation analysis investigates the relationship between lithium carbonate spot price and electric vehicle sales. The core analysis of this research is regression analysis, and it is used to study the dependency of GDP per capita and incentives, along with lithium carbonate price to electric vehicle sales. The comparison between markets in their electric vehicle sales leads to an observation that even though emerging markets had some higher electric vehicle sales, their mean per month is lower than in developed markets. From the findings, it can be observed that there are differences in consumer patterns between the markets, emerging and developed, in terms of electric vehicles sales. This is in line with what the theory of income elasticity of demand suggests. It is also found that there is a weak but negative correlation between lithium carbonate spot price and EV sales, which aligns with the law of supply and demand theory. However, the findings indicate a delayed cost pass-through between them. Overall, the results suggests that higher income market, developed market, is related to higher electric vehicle sales, but it does not change the strength how lithium carbonate price impacts electric vehicle sales.

Kasvavien kestävyystavoitteiden myötä sähköautojen suosio on kasvanut, koska niitä pidetään polttomoottoreita ekologisempana vaihtoehtona. Kuitenkaan aiempia tutkimuksia litiumkarbonaatin hinnan ja sähköautojen myynnin välisestä suhteesta eri markkinoilla ei ole havaittu. Tämän tutkimuksen tarkoituksena on siis analysoida litiumkarbonaatin hinnan vaihteluiden vaikutusta sähköautojen myyntiin. Koska eri markkinoiden välillä on eroja kuluttajakäyttäytymisessä ja ostovoimassa, tuloksia verrataan nousevan talouden markkinoiden ja kehittyneiden markkinoiden välisiin eroihin. Tämän lisäksi tutkitaan litiumkarbonaatin hinnan mahdollisuutta ennustaa sähköautojen myyntiä eri markkinoilla. Tutkimuksessa valitaan kolme eri maata markkinaa kohden, joiden sähköautojen myyntitilastoja analysoidaan vuosilta 2021–2024. Tämän lisäksi otetaan huomioon bruttokansantuotetta henkeä kohden, sekä erilaisia kannustimia sähköautojen ostoon. Kvantitatiivisen tutkimus menetelmän avulla julkisista lähteistä saatavaa tietoa analysoidaan useiden tilastollisten analyysimenetelmien, sekä erilaisten teorioiden, kuten kysynnän ja tarjonnan, hinnan välittymisen, ja kysynnän tulojouston avulla. Tutkimuksessa käytetyt kuvailevat tunnusluvut antavat yleisen kuvan tutkimuksessa käytettävästä tiedosta ja niiden kehityssuunnasta, mitkä auttavat luomaan pohjan seuraaville analyyseille hypoteesin testausta varten. Vertaileva analyysi puolestaan vertaa eri markkinoiden välisistä suhteista litiumkarbonaatin ja sähköautojen välillä. Korrelaatioanalyysin avulla tutkitaan yleisesti litiumkarbonaatin hinnan ja sähköautojen myynnin välistä suhdetta. Tutkimuksen pää analyysimenetelmänä toimii regressioanalyysi, jonka avulla tarkastellaan bruttokansantuotetta henkeä kohden, litiumkarbonaatin hinnan ja erilaisten kannustimien riippuvuutta sähköautojen myyntiin. Vertailu sähköautojen myynnin ja markkinoiden välillä johti päätelmään, että vaikka nousevan talouden markkinoilla oli tilanteita, missä eri maiden kuukausitasoinen myyntinsä oli korkeampi, oli heidän sähköautojen kokonaismyynninkeskiarvo kehittyneitä markkinoita pienempi. Tästä voidaan päätellä, että markkinoiden välillä on eroavaisuuksia kuluttajakäyttäytymisessä sähköautojen myynnin osalta. Tämä on linjassa kysynnän tulojousto teorian kanssa. Tämän lisäksi tutkimus osoittaa, että litiumkarbonaatin ja sähköautojen myynnin välillä on heikko, mutta negatiivinen korrelaatio, mikä puolestaan vastaa kysynnän ja tarjonnan lakia. Tutkimuksessa on kuitenkin löydetty viitteitä, että litiumkarbonaatin ja sähköautojen myynnin välillä on viivästynyt kustannusten siirtyminen. Yleisesti voidaan todeta, että tulokset esittävät kehittyneiden markkinoiden liittyvän korkeampiin sähköajoneuvomyynteihin, mutta sillä ei kuitenkaan ole vaikutusta litiumkarbonaatin hinnan ja sähköautojen välisessä suhteessa.
Keywords: electric vehicles; lithium; economic development; supply; demand; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management